The effects of elite sports participation on later job success - Ralf Dewenter; Leonie Giessing (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
This paper analyses the income effect of the participation in elite sports using a unique dataset on former German top-level athletes. To quantify the average treatment effect we use covariate nearestneighbour matching. While our treatment group consists of formerly top-level athletes the control group of non-athletes is drawn from the GSOEP database. On average, former athletes receive higher incomes than similar non-athletes. Moreover, team sports athletes as well as male athletes realise significantly higher incomes. Comparing the income of former female athletes with male non-athletes, we find that participating in elite sports closes the gender-wage gap.
Keywords: 330